Undergraduates shared culture and academic activities in Thailand - Darolhisam, Darus

(untitled)
A total of 140 Universiti Malaysia Pahang (UMP) undergraduates spent three days at Kampung Tammalang Hilir Satun in Thailand under a community service programme beginning December 14, 2012.